Penerapan Model UTAUT 2 Terhadap Perilaku Penggunaan E-Filing - Suarna Dwipa, Putu Andy; Gayatri, Gayatri (E-Jurnal Akuntansi, 2025)
The research conducted has a focus on knowing the factors that influence the intention and behavior of using e-Filing through the application of the UTAUT 2 Model. This research was conducted at Denpasar Barat and Denpasar Timur Tax Office. The sampling method used is purposive sampling with a sample of 100 respondents who have met the criteria as a sample. Structural Equation Model-Partial Least Square is used for data analyzing. The findings obtained indicate that the intention to use e-Filing is supported by business expectations, socio-cultural factors, beliefs and is not supported by habits and usage intentions.  Keywords: UTAUT 2; e-Filing; Intention; Usage Behavior